Urban Microplastics Emissions: Effectiveness of Retention Measures and Consequences for the Baltic Sea - Schernewski, Gerald; Radtke, Hagen; Hauk, Rahel; Baresel, Christian; Olshammar, Mikael; Oberbeckmann, Sonja (Frontiers in Marine Science, 2021)
Urban sewage water pathways seem most important for microplastics emissions to the Baltic Sea. We use microplastics emission data for the entire Baltic Sea region, calculate emissions for three sewage water related urban pathways and develop emission scenarios for the majority of microplastics particles. All plastics are divided into potentially floating (density 0.8–1.0 g/cmł) and sinking (1.1–1.5 g/cmł) polymers and we address the size class of 20–500 μm. 6.7 × 1013 microplastics particles enter the Baltic Sea annually from urban pathways. 62% result from stormwater runoff including sewer overflow, 25% from wastewater treatment plants (WWTPs) and 13% from untreated wastewater. The emission scenarios serve as input for 3D-model simulations, which allow estimating transport, behaviour and deposition in the Baltic Sea environment. Our model approach suggests average annual microplastics concentrations in the water body of the central Baltic Sea of 1–4 particles/m2 sea surface and 1 particle/m3 in the upper 2 m sea surface layer. The majority of the particles is accumulated in upper sea surface layers. The model suggests that only between 6% (Arcona Basin) and 21% (Gotland Basin) of the particles are below a depth of 25 m. In coastal waters, the concentrations can exceed 10 particles/m3 in the upper 2 m surface water layer (e.g., Gulf of Riga, Gulf of Gdańsk) and 1 particle/m2 on the sediment surface. Usually within weeks, emitted microplastics are washed ashore causing annual coastal accumulations of up to 109 particles/m coastline within a few kilometres distance to emission sources. On average, above 106 particles/m are annually accumulated and trapped at coasts around the Baltic Sea. The reduction of the annual sewer overflow from presently 1.5% of the annual wastewater loads to 0.3% would reduce the total emissions to the Baltic Sea by 50%. If all sewage water would be connected to WWTPs and undergo a tertiary treatment, a reduction of 14.5% of the total emissions could be achieved. The effect of retention in rivers seems limited in the Baltic Sea region, because near coast emissions contribute around 50% of the total microplastics emissions.